Analisis Kebutuhan Komik Islami sebagai Suplemen Media Pembelajaran Sistem Sirkulasi untuk SMA/MA: (Analysis of the Requirement for Islamic Comic as a Supplement of The Circulation System Learning Media for SMA/MA) - Andara Vasya Mardiah; Relsas Yogica Relsas Yogica (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
MAN 2 Padang is a school that has different characteristics from the usual public schools. The school which is under the auspices of the Ministry of Religion has an Islamic nuance with its vision, namely